Some methods to stain cartilage and bone of vertebrates and application on small fish in museum of oceanography - Ngan, Nguyen Thi My; Nghi, Bui Quang; Phu, Nguyen Kha; Ben, Hoang Xuan (Vietnam Journal of Marine Science and Technology, 2019)
In a natural scientific museum as Museum of Oceanography, a specimen should be not only awesome but also scientific in order to attract visitors and introduce knowledge to them. One of the methods satisfying those requirements is “Method of staining cartilages and bones for small vertebrates”. This method was applied to handle small fish: Anchovies (Encrasicholina devisi (Whitley, 1940)), amphiprions (Amphiprion ocellaris (Cuvier 1830)) and ponyfish (Leiognathus sp.), which is highly efficient, not only used in studying fish bones and cartilages but also attractive to visitors. This paper also gives details on experiences during handling process of this method.